1997
DOI: 10.1007/pl00005013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-701,324, a high-affinity antagonist at the N-methyl-D-aspartate (NMDA) receptor glycine site, on the rat electroencephalogram

Abstract: L-701,324 (7-chloro-4-hydroxy-3-(3-phenoxy) phenyl-2-(1H)-quinolone) is a novel, orally active antagonist at the N-methyl-D-aspartate (NMDA) receptor glycine site. As NMDA receptor antagonism is generally associated with anaesthetic effects, we have examined the electroencephalographic alterations produced by doses of L-701,324 that effectively reduce NMDA-evoked responses in vivo. Microdialysis probes incorporating an electrode were implanted in the striatum of rats and perfused with artificial cerebrospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The EEG data confirm this finding (i.e., lack of effect on NMDA receptor function), because the slight changes in cortical EEG that we observed (Fig. 5) do not correspond to those previously found with the high‐affinity antagonist of the NMDA receptor glycine site, L‐701,324 (Obrenovitch et al, 1997 a ). NMDA receptor block is known to potentiate halothane anaesthesia (McFarlane et al, 1995), and this was shown on the EEG in our previous study by an increase in low‐frequency amplitude and a reduction in the high‐frequency components (Obrenovitch et al, 1997 a ).…”
Section: Effects Of Ro 61‐8048 On Nmda‐induced Depolarisations and Spsupporting
confidence: 71%
See 2 more Smart Citations
“…The EEG data confirm this finding (i.e., lack of effect on NMDA receptor function), because the slight changes in cortical EEG that we observed (Fig. 5) do not correspond to those previously found with the high‐affinity antagonist of the NMDA receptor glycine site, L‐701,324 (Obrenovitch et al, 1997 a ). NMDA receptor block is known to potentiate halothane anaesthesia (McFarlane et al, 1995), and this was shown on the EEG in our previous study by an increase in low‐frequency amplitude and a reduction in the high‐frequency components (Obrenovitch et al, 1997 a ).…”
Section: Effects Of Ro 61‐8048 On Nmda‐induced Depolarisations and Spsupporting
confidence: 71%
“…This concentration of NMDA was reduced to 150 μ M with urethane to minimise the occasional occurrence of spreading depression that had been observed with 200 μ M NMDA in preliminary experiments carried out with this anaesthetic (Saito et al, 1995). Using the same experimental procedure, inclusive of halothane anaesthesia, we previously demonstrated that known glycine‐site receptor antagonists (i.e., L‐701,324 and KYNA) inhibited the responses evoked by 2‐min perfusion of NMDA, in a concentration‐dependent manner (Obrenovitch et al, 1997 a ; Urenjak and Obrenovitch, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMDA receptors participate in the development of the CNS (Colonnese et al, 2005;Colonnese and Constantine-Paton, 2006;Kelsch et al, 2012). In addition, overactivation of NMDA receptors can promote seizures and cell death (Choi, 1994;Rothman and Olney, 1995;Obrenovitch et al, 1997;Dirnagl et al, 1999;Yurkewicz et al, 2005), and NMDA receptor hypofunction is a leading hypothesis for schizophrenia (Coyle, 2012;Menniti et al, 2013). Thus, there is considerable interest in factors that control NMDA receptor expression and function.…”
Section: Gaba/glutamate Receptor Mutations In Neurologic Diseasesmentioning
confidence: 99%
“…NMDARs are Ca 2+ ‐permeable, voltage‐dependent receptors that mediate a slow synaptic current and are blocked by extracellular magnesium . The overactivation of NMDARs has been implicated in the induction of seizures and cell death, whereas hypofunction of this receptor may contribute to schizophrenia …”
mentioning
confidence: 99%